2015
DOI: 10.1108/ijoem-02-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying industry beta in Indian stock market and forecasting errors

Abstract: Purpose – The purpose of this paper is to empirically estimate industry beta in Indian stock market with three alternative models and compare the accuracy of forecasting error to find the most suitable model for time-varying beta estimation. Design/methodology/approach – The paper applies the standard regression model, Kalman filter model, other statistical approaches and secondary material. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This study found that systemic risk ( β ) is not constant over the studied sample period as it is time varying in nature, which indicated that developing countries stock markets are volatile and dynamic in nature. This was in line with the study finding of Das and Barai (2015) that Indian stock markets are volatile in nature.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that systemic risk ( β ) is not constant over the studied sample period as it is time varying in nature, which indicated that developing countries stock markets are volatile and dynamic in nature. This was in line with the study finding of Das and Barai (2015) that Indian stock markets are volatile in nature.…”
Section: Discussionsupporting
confidence: 92%
“…Mollik and Bepari (2010) tested the applicability of CAPM for 110 stocks listed at Dhaka stock exchange and found beta to exhibit both interperiod as well as intra-period non-stationarity. In Indian context, Shah and Moonis (2003) and Das and Barai (2015) found evidence in support of beta being a time-varying phenomenon affected by extreme global events hitting the stock market.…”
Section: Testing the Dynamics Of Alpha And Beta Coefficients During The Two Market Conditionsmentioning
confidence: 98%
“…To understand the role of beliefs in consumer behaviour, Gopi and Ramayah (2007), based on of theory of planned behaviour, concluded that attitude, subjective norm and perceived Lee and Tai (2006), Rajagopal (2007), Gopi and Ramayah (2007), Saffu and Scott (2009), Lee and Tai (2009), Srivastava (2010) Adaoglu and Katircioglu (2013), Das and Barai (2015), Ahmed (2017) Bonaglia and Goldstein (2006), Todd and Javalgi (2007), Baack and Boggs (2008), Singh et al (2010), Varma (2011, Singal andJain (2012), Binachi (2014), Cassia and Magno (2015), Wan et al (2015), Chaves (2018) (continued ) Rajagopal (2007) illustrated that strategic product positioning and effective retailing enhance consumer perception of organic products to understand green consumerism. Issock et al (2020) enumerated that consumption values, to some extent, impact green customer satisfaction, resulting in green customer trust and loyalty and positive word of mouth.…”
Section: Cluster 1: Consumer Behaviourmentioning
confidence: 99%
“…To investigate the weekend effect, Al-Khazali et al (2010), using the stochastic dominance (SD) approach, concluded that the Saturday effect is not exhibited in three Gulf Stock Markets. Das and Barai (2015) calculated the beta in the Indian stock market using regression and, further using the Kalman filter model, analysed the influence of the global economic environment on the riskiness of Indian markets. To understand the impact of political uncertainty on market behaviour, Ahmed (2017) found that political uncertainty profoundly impacts the risk-return profile of all sectors of Egypt's equity market behaviour.…”
Section: Cluster 2: Financial Marketsmentioning
confidence: 99%